2019
DOI: 10.1002/ppul.24225
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath temperature as a tool for monitoring asthma control after an attack in children

Abstract: Background Exhaled breath temperature (EBT) has been suggested as a non‐invasive marker of airway inflammation in asthma. There have been no studies examining longitudinal changes in EBT following asthma attacks. Objective To investigate changes in EBT during and after an asthma attack and to relate these changes to changes in respiratory physiological measurements. Methods We evaluated 38 hospitalized children aged 5‐18 years diagnosed with an asthma attack. Spirometry was performed upon hospitalization. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that the EBT of patients with asthma is higher than that of healthy subjects (22,23). These studies reported a correlation between EBT and the level of exhaled nitric oxide, which is an inflammatory marker present in asthmatics (24).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have reported that the EBT of patients with asthma is higher than that of healthy subjects (22,23). These studies reported a correlation between EBT and the level of exhaled nitric oxide, which is an inflammatory marker present in asthmatics (24).…”
Section: Discussionmentioning
confidence: 93%
“…It has previously been hypothesized that the level of EBT is related to the degree of airway inflammation (22,23,28,29). Previous studies have shown that EBT is increased in asthmatic children (30)(31)(32)(33) and in patients with non-small cell lung cancer (34), as well as in patients exhibiting exacerbated COPD (35); therefore, patients who presented with the aforementioned diseases were excluded in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A group of investigators measured exhaled breath temperature amongst children hospitalized with an asthma exacerbation as well as upon recovery. 10 They found that there was a significant decrease in exhaled breath temperature after recovery from the asthma exacerbation as well as correlation with peak expiratory flow rate. However, in individual patients, exhaled breath temperature did not correlate with FEV1, fractional excretion of nitric oxide, or sputum eosinophil count.…”
Section: Monitoring Testsmentioning
confidence: 97%
“…One such modality is exhaled breath temperature. A group of investigators measured exhaled breath temperature amongst children hospitalized with an asthma exacerbation as well as upon recovery 10 . They found that there was a significant decrease in exhaled breath temperature after recovery from the asthma exacerbation as well as correlation with peak expiratory flow rate.…”
Section: Monitoring Testsmentioning
confidence: 99%